The effect of leadership style and organizational climate on employee performance at PT Cipta Baja Trimatra - Supardi, Supardi; Yulianah, Yulianah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This research was conducted at PT Cipta Baja Trimatra with the intention of determining whether or not there is a correlation between the employees' level of work performance and the leadership style of the company's management. The survey had a total of 52 employees from PT Cipta Baja Trimatra participate as respondents. The research was carried out on employees at that company. The method of random accident sampling was used to choose the research respondents. The distribution of questionnaires and a search of the relevant literature were the methods used to obtain the data. Multiple linear regression is the method for analyzing the data, while SPSS for Windows 22.0 is the statistical software that was utilized. At PT Cipta Baja Trimatra, the results of the test indicate that leadership style has a positive and significant effect on employee job satisfaction, and that organizational climate also has a positive and significant effect on employee job satisfaction. Both of these factors contribute to employee job satisfaction. In addition, the study discovered that the influence of leadership style and organizational climate variables on employee performance was quite little, coming in at 10.8 percent.